Room temperature electron-mediated ferromagnetism in a diluted magnetic semiconductor: (Ga,Mn)N - Huh, KS; Ham, MH; Myoung, JM; Lee, JM; Lee, KI; Chang, JY; Han, SH; Kim, HJ; Lee, WY (INST PURE APPLIED PHYSICS, 2002)
We present the electron-induced ferromagnetic ordering and magnetotransport of epitaxial (Ga1-xMnx)N films with low Mn concentration (x = 0.0006-0.005) grown by plasma-enhanced molecular beam epitaxy (PEMBE). The (Ga,Mn)N films were found to exhibit n-type conductivity, ferromagnetic ordering with Curie temperature in the range 550-700K, in-plane magnetic anisotropy, and negative magnetoresistance (MR) in the range of 4-300 K. Our results are indicative of ferromagnetic semiconducting (Ga,Mn)N films due to the coupling of electron spins and localized Mn moments.
Keywords: MOLECULAR-BEAM-EPITAXY; HETEROSTRUCTURES